The Role of Perceptual Interference, Semantic Interference, and Relational Integration in the Development of Analogical Reasoning - Yu, Xiao; Geng, Liuna; Chen, Yinghe; Han, Congcong; Zhu, Xiaojing (Frontiers in Psychology, 2020)
This study aimed to examine the role of perceptual interference, semantic interference, and relational integration (RI) in the development of analogical reasoning, and to compare the interactive pattern of interference and RI in children and adults. In Experiment 1, we tested 31 3- and 4-year-olds, 27 5- and 6-year-olds, and 40 adults for perceptual interference and RI in analogical reasoning. Perceptual interference emerged when proper mapping between analogically matching objects was incoherent with their perceptual features. RI was evaluated via manipulation of the number of objects in an analogical scene. Significant main effects of perceptual interference and RI were found in children and adults. In Experiment 2, we tested 30 3- and 4-year-olds, 27 5- and 6-year-olds, and 40 adults for semantic interference and RI in analogical reasoning. Semantic interference emerged when proper mapping between analogically matching objects was incoherent with their categorical features. Results showed significant main effects of semantic interference and RI in children and adults. The results of both experiments suggested different mechanisms of interference and RI in children and adults. For children, interference and RI depended on shared cognitive sources. If one factor (i.e., interference resolution) needed more cognitive demand, there would be limited resources available for another factor (i.e., RI). Furthermore, for adults, the increased load of RI and interference on adults’ analogical reasoning exceeded the sum of their respective singular effects. For 3- and 4-year-olds, the degree of perceptual interference was larger than the degree of semantic interference in the Binary Relation condition, whereas there was no significant difference between the degree of two types of interference in the Quaternary Relation condition. Moreover, for 5- and 6-year-olds, the degree of semantic interference was larger than the degree of perceptual interference in both relation conditions. For adults, there was no difference between the degree of two types of interference in both relation conditions. The article also discusses the theoretical and practical implications of this research.